PENGELOLAAN PROGRAM UNGGULAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH KEJURUAN BERBASIS PESANTREN - Akhmad Masduqi (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2021)
This research aims to understand and analyze the management of the flagship program of Islamic Religious Education at SMK Nurul Hidayah Al-Falah Mojokerto in facilitating students to contribute to society. This research uses a qualitative approach to the type of case study, where data collection is done through interviews, observation, and documentation. While the data analysis is done through display data, data reduction, and conclusion. The results showed that the management of the Islamic Religious Education's flagship program at SMK Nurul Hidayah Al-Falah Mojokerto in facilitating students to contribute to society was carried out in a planned and systematic manner through strengthening the Islamic Education extracurricular program as a superior program in the institution, which has types of activities. All of these activities are carried out through careful planning and are carried out concerning existing plans and evaluated with the principle of continuous improvement.